Endogenous capital productivity in the Kaleckian growth model. Theory and Evidence - Christian Schoder (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
An endogenous, pro-cyclical capital productivity is motivated by optimizing firm behavior and estimated for a panel of US industries. A positive and significant adjustment parameter has been found relating the growth rate of capital productivity to the difference between the realized utilization rate and the target rate. The endogenous capital productivity is then introduced to a simple Kaleckian growth model with constant rate of utilization in the long run. The effects of shocks to investment, consumption and distribution are studied. We show that the paradox of thrift and the paradox of cost may only hold if Harrodian instability is introduced accompanied by stabilizing counter-forces such as debt dynamics.
urn:nbn:de:101:1-2013031310798
Keywords: E12; E22; C22; 330; Kaleckian growth model; effective demand; stationary utilization rate; endogenous capital productivity; panel estimation